2006
DOI: 10.1590/s0004-282x2006000500023
|View full text |Cite
|
Sign up to set email alerts
|

Doppler transcraniano convencional em voluntários assintomáticos: variabilidade e valores de referência para parâmetros de fluxo sanguíneo

Abstract: RESUMO - Reference values for measures of blood flow velocities and impedance indexes in healthy individuals through conventional transcranial DopplerABSTRACT -Objective: To establish reference values for measures of blood flow velocities and impedance indexes in healthy individuals through conventional transcranial Doppler (TCD) and to observe their variations in relation to the age and sex. Method: 88 asymptomatic volunteers were examined without antecedents of cardiac, peripheral or cerebrovascular diseases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 24 publications
3
4
1
1
Order By: Relevance
“…This finding differs from a previous study 12 , but in that study participants were adults (predominantly women) without chronic disease. In our data there is not difference in cerebral arteries mV between genders in SCD patients, similarly to previous study in children 8 .…”
Section: Discussioncontrasting
confidence: 99%
“…This finding differs from a previous study 12 , but in that study participants were adults (predominantly women) without chronic disease. In our data there is not difference in cerebral arteries mV between genders in SCD patients, similarly to previous study in children 8 .…”
Section: Discussioncontrasting
confidence: 99%
“…On the other hand, in equine females the PI variable showed positive correlations with RI, SV, age and longitudinal and transversal diameter, and negative correlation with DV, that is, a positive correlation was observed between the PI and body mass in mules. As for female equines, that correlation was observed with age, as found by Aguiar (2015) in equines and Barbosa et al (2006) in humans.…”
Section: Discussionsupporting
confidence: 73%
“…Regarding spectral Doppler parameters, it was observed that the RI variable of mules showed a positive correlation with PI, SV and body mass, and negative correlations with DV and transversal diameter. In equine females there were positive correlations with PI, SV, VFI, age and longitudinal and transversal diameter, and negative correlation with DV, that is, there was a positive correlation between the variable RI with body mass in mules, while in equine females that correlation is with age, as reported by Aguiar (2015) in equines and by Barbosa et al (2006) in humans. A positive correlation was also found between RI and the longitudinal and transversal diameter of the neck in equine females, while in mules this correlation was negative.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…A ferramenta do doppler transcraniano pode ajudar a identificar sinais de embolia numa fase não protegida (antes do uso do filtro) ou durante a passagem do filtro ou identificar a embolia no momento da aplicação do "stent" ou do balão ou ainda na remoção do filtro (Angelini et al, 2002;Vos et al, 2005). Também o doppler transcraniano é capaz de fornecer informações sobre fluxo dos vasos do polígono (Barbosa et al, 2006) e demonstrar alterações após angioplastia em segmento cervical (Fregni et al, 2003). Porém a avaliação por doppler tem a desvantagem de avaliar apenas um vaso, geralmente a artéria cerebral média ou a artéria carótida interna cervical distal do lado da estenose carotídea, deixando um vasto território cerebral não coberto na avaliação de fenômenos embólicos.…”
Section: Tratamento Da Estenose Carotídea Por Angioplastia E Implanteunclassified